Looking for the Impossible: The Futile Search for a Balanced Doctrine of Humanitarian Intervention - A. Grigoryan (Международная аналитика)
Many in the West, especially in the human rights community, saw the end of the Cold War as a great opportunity for a normative transformation in international relations. They argued that the concept of sovereignty was an anachronism and that a new international regime should be created allowing for easier intervention against states that subject their citizens to violence. It seemed like a relatively straightforward issue of clashing normative principles at fi rst. As the conversation about interventions has evolved, however, it has become increasingly clear that the problem is much more complex. This article examines the set of complex trade-off s between various values and norms related to humanitarian intervention and demonstrates that no interventionist doctrine that balances these values and norms is possible. It empirically examines these tensions in the context of interventions in Kosovo and Libya.